NICHE MARKETING OF LETTUCE - TRINIDAD - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
In Trinidad vegetables and short-term root crops are largely the province of small farmers operating on farms of 0.2 ha to 2 ha, with the great majority on less than 1 ha. Given the small land area, high value, quick growing crops offer the best...